Rebuilding communities with empathy. Issue 1 (2nd January 2020) - Berardi, M. Kate; White, Annie M.; Winters, Dana; Thorn, Kaila; Brennan, Mark; Dolan, Pat
ABSTRACT: Throughout 2020, our lives and communities have been turned upside down due to the challenges and disruptions surrounding COVID-19, global protests around racism and racial inequality and political polarization. All pose a direct threat to local community well-being, our wider society, and to the collective, democratic processes by which we achieve local development. Inspired by the words of humanitarian Fred Rogers, our group of empathy researchers examine how simple and deep interactions between individuals can intentionally benefit individuals and form the foundations that build stronger communities. In this article we will: (1) Explore the importance of applied empathy to individual and community well-being; (2) explore the critical interrelationship between interaction, empathy, and positive social development/change; and (3) provide a framework for maximizing empathy and interaction in both responses to the immediate crises and in the longer-term process of community building.